Solutions supporting the strategy implementation – model proposal - Wołczek, Przemysław (Rozwiązania wspierające realizację strategii – ujęcie modelowe, 2019)
The purpose of the article is to present the results of empirical research concerning solutions used in the strategy implementation process by companies recognized as effective in achieving their strategic goals. Based on the results of the research, a model of improving the strategy implementation process was proposed. In the theoretical part the method of analysis and critical review of the literature was used. The technique used in the empirical study was PAPI. In order to investigate relationships, Cramer’s V coefficient was calculated. The main findings of the study allow us to conclude that there are some specific solutions from the following areas: organisational structure, communication and motivation, cooperation, implementation tools and methods, and control, which particularly effectively support the strategy implementation
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 2, s. 49-59
Keywords: strategy; strategy implementation; model; strategia; wdrożenie strategii